Analysis, Occurrence and Exposure Evaluation of Antibiotic and Anthelmintic Residues in Whole Cow Milk from China - Liming Chang; Sishi Du; Xiaojiao Wu; Jian Zhang; Zhiwei Gan (Antibiotics, 2023)
An optimized QuEChERS method for the simultaneous extraction of 26 antibiotics and 19 anthelmintics in whole cow milk was established, followed by UHPLC-MS/MS analysis. Briefly, 20 mL acetonitrile with 1 g disodium hydrogen citrate, 2 g sodium citrate, 4 g anhydrous MgSO4, and 1 g sodium chloride were added to 10 g milk for target chemical extraction, followed by 50 mg anhydrous MgSO4 for purification. Satisfactory recoveries were obtained using the modified QuEChERS method, with recoveries of the antibiotics ranging from 79.7 to 117.2%, with the exception of norfloxacin, which was at 53.4%, while those for anthelmintics were in the range of 73.1–105.1%. The optimized QuEChERS method presented good precision, with relative standard deviations ranging from 7.2 to 18.6% for both antibiotics and anthelmintics. The method was successfully applied to analyze the antibiotics and anthelmintics in 56 whole cow milk samples from China. Briefly, the detection frequencies and concentrations of most of the antibiotics and anthelmintics were low in the whole cow milk samples, with concentrations ranging from below LOD to 4296.8 ng/kg. Fenbendazole, febantel, enrofloxacin, levofloxacin, sulfadiazine, and sulfamethoxazole were the predominant drug residues in the whole cow milk samples. Spatial distribution was found for those antibiotics and anthelmintics with detection frequency higher than 50%, especially for the antibiotics, indicating regional differences in drug application. Based on the current study, exposure to antibiotics and anthelmintics through whole cow milk consumption are lower than the acceptable daily intake values suggested by the China Institute of Veterinary Drug Control. However, long-term exposure to low doses of antibiotics and anthelmintics still needs attention and merits further study.